2017
DOI: 10.1101/lm.044131.116
|View full text |Cite
|
Sign up to set email alerts
|

Input from the medial geniculate nucleus modulates amygdala encoding of fear memory discrimination

Abstract: Generalization of fear can involve abnormal responding to cues that signal safety and is common in people diagnosed with post-traumatic stress disorder. Differential auditory fear conditioning can be used as a tool to measure changes in fear discrimination and generalization. Most prior work in this area has focused on elevated amygdala activity as a critical component underlying generalization. The amygdala receives input from auditory cortex as well as the medial geniculate nucleus (MgN) of the thalamus, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 46 publications
0
28
0
Order By: Relevance
“…Moreover, 104.25 V/m of field strength (50%) additionally reaches the Hyp, the whole ic, the mmt, the fct, parts of the ml and GPi, the bic, the al, parts of the reticular thalamic nucleus (R) and the whole pulvinar (Pul), MGN and LGN. Given the fact that Figure 2 proves an unexpected extension of electrical current to geniculate thalamic and pulvinar areas, changes in emotion perception could be attributed to impaired visual and auditory processing ( Péron et al, 2010 , 2013 ; Symons et al, 2016 ; Ferrara et al, 2017 ).…”
Section: Resultsmentioning
confidence: 93%
“…Moreover, 104.25 V/m of field strength (50%) additionally reaches the Hyp, the whole ic, the mmt, the fct, parts of the ml and GPi, the bic, the al, parts of the reticular thalamic nucleus (R) and the whole pulvinar (Pul), MGN and LGN. Given the fact that Figure 2 proves an unexpected extension of electrical current to geniculate thalamic and pulvinar areas, changes in emotion perception could be attributed to impaired visual and auditory processing ( Péron et al, 2010 , 2013 ; Symons et al, 2016 ; Ferrara et al, 2017 ).…”
Section: Resultsmentioning
confidence: 93%
“…Doubling the shock strength significantly increased the percentage of the units responding to both auditory stimuli, shifting the balance toward a greater proportion of generalizing over cue‐specific cells. These changes that translate to an elevated freezing response to both the paired and unpaired auditory stimulus appears to be dependent on protein synthesis‐dependent plasticity in medial geniculate and subsequent changes in the expressions of AMPA receptor and synaptic scaffolding proteins at their amygdala synapses (Ferrara, Cullen, Pullins, Rotondo, & Helmstetter, ). Clearly, a thorough understanding of the cells giving rise to these thalamoamygdalar projection from the MGM/PIN is vital to our understanding and treating such debilitating conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The contributions of these brain regions have mostly been ignored in the context of fear-related behavior. At the level of the thalamus, studies have demonstrated that the auditory thalamus influences fear generalization (25,26) and that the paraventricular thalamus influences fear conditioning and fear memory retrieval (27,28). Most recently, the zona incerta (ZI), a sub-thalamic region, has received attention for its role in modulating defensive responses and retrieval of fear-related memories (29,30).…”
Section: Introductionmentioning
confidence: 99%